Introduction to Architectural Science : The basis of sustainable design - Szokolay, S. V. (Steven Vajk), 1927-; Brisbin, Christopher (Oxford : Architectural, 2004)
By introducing the basics of architectural science, this reference book provides an understanding of the physical basis of architectural design. Each chapter presents an outline of the relevant physics of heat, light, sound and energy, followed by an examination of human requirements.
Includes bibliographical references (p. 243-245) and index.
Keywords: Architectural design; Buildings -- Environmental engineering; Sustainable architecture; Architecture and Planning